Quantitative measurement of gas wettability of different substrates. Issue 4 (16th February 2016) - Zhang, Min; Jiang, Guancheng; Luo, Shaojie; Tang, Xinguo; Xing, Xiaoxuan; Pang, Jiangtao; Xie, Shuixiang
ABSTRACT: Both theory and experiments demonstrate that gas-wetness cannot always be overlooked and the gas-wet degree affects gas-well production greatly in gas condensate reservoirs. In the study, two quantitative methods have been introduced, the sessile drop and the captive bubble, and the corresponding wettability indexes, including gas-wetting parameter in the sessile drop method and gas contact angle in the captive bubble method. Gas-wetness of various substrates, such as Paraffin wax, plastics, glass, and iron plate, has been compared. Experimental results show that with the decrease of surface free energy, the hydrophobic and oleophobic and aerophily property gets enhanced. Particularly, air against water was preferentially wet on the Paraffin wax surface ( = 0.258, = 70.53°). Moreover, gas-wetness against water on the substrate surface is stronger than gas-wetness against oil on the same surface. The study is of great importance for study on gas-wetness.